IMPLEMENTASI NILAI-NILAI TRI HITA KARANA PADA BIDANG USAHA PENGGEMUKAN SAPI DI DESA BLUMBANG - Suka, I.G; Wiasti, NM.; Suarsana, N.; Miwada, IN.S. (Buletin Udayana Mengabdi; Vol 12 No 2 (2013): Volume 12 No.2 – September 2013, 2013)
This Community service was carried out in the village Blumbang, sub Kerambitan, Tabanan on Saturday, September 22nd, 2012 at 15:00 to 17:00 pm. The participants included members of the village community of Blumbang who joined in the cattle ranchers. From discussions with the members of the group , it can be said that they have a grasp of the concept of THK (Tri Hita Karana) but almost 100% of the participants attending this activity have not yet known how to implement. Activities continued with the introduction of fermentation technology to solve the problem. All the participants were very enthusiastic. Conclusion could be drawn that the introduction of THK concept activities and its implementation in their daily life of the village community has opened Blumbang villagers’ minds. Insight into the importance of processing the feces and urine of cow breeding is as a real form of the THK concept application